BOARD GENDER DIVERSITY, CORPORATE REPUTATION, AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: EVIDENCE FROM SRI-KEHATI INDEX COMPANIES - Mutiara Rachma Ardhiani; Fairuza Arindra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to examine the impact of Board of Directors Gender Diversity and Corporate Reputation on CSR Disclosure among companies listed on the SRI-KEHATI index on the Indonesia Stock Exchange for the period 2019-2024. The research sample was selected through a purposive sampling technique, focusing on companies listed on the SRI-KEHATI index. The study used multiple linear regression to analyze the data. The results showed that Board of Directors Gender Diversity had no significant effect on CSR Disclosure, while Corporate Reputation showed a positive and significant effect on CSR Disclosure. These results indicate that corporate reputation is a factor that motivates companies to increase transparency in their social responsibility disclosure, while gender diversity on the company's board of directors does not directly affect the level of CSR disclosure. This study adds to existing research on corporate governance and corporate social responsibility, particularly in terms of how corporate reputation can encourage transparency in CSR reporting.